Experimental assessment of the effects of biaxial bending moment and axial force on reinforced concrete corner columns. (5th February 2018) - Dang, Hoang V.; Lee, Kihak; Han, Sang W.; Kim, Sung J.
Abstract : In this research, corner columns of low‐rise residential buildings, which might be unstable and vulnerable to seismic loadings during earthquake due to vertical and horizontal irregularities, are tested under different effects from bending moment and axial force. Here, biaxial loading is focused and developed, representing a rhombus path with 100% force in the main direction, versus 30% force in the perpendicular direction. Two of eight test specimens are subjected to axial compressive force at 30% of column capacity, while other specimens are at 10%. The eight test specimens were constructed with varying transverse reinforcement details, to control the column‐failure mechanism. The objective of this research was to investigate the seismic behavior of the corner columns of low‐rise buildings that used ordinary‐moment‐resisting‐frames (OMRF). The test results were discussed to interpret the effect of biaxial loading on the overall performance of the columns using comparison between global and local responses. It could be very helpful in deeply understanding the seismic behavior of structures which were designed in accordance with OMRF requirements. Furthermore, this information might affect decisions about using intermediate‐moment‐resisting frames or special‐moment‐resisting frames, where more demanding seismic requirements are applied.